THE EFFECT OF DIRECTED READING THINKING ACTIVITY (DRTA) STRATEGY ON STUDENTS’ READING COMPREHENSION ABILITY OF RECOUNT TEXT AT GRADE ELEVEN OF SMA NEGERI 4 PEMATANG SIANTAR - Vivi Grasela Nainggolan; Asima Rohana Sinaga; Irene Adryani Nababan (Jurnal Scientia, 2023)
The objective of this research is to find out the effect of Directed Reading Thinking Activity (DRTA) strategy on students' reading comprehension ability of Recount Text at Grade Eleven of SMA Negeri 4 Pematang Siantar in the academic year 2023/2024. This research uses a quantitative method with quasi-experimental design. It has two classes, namely experimental class and control class. 353 students in grade eleven at SMA Negeri 4 Pematang Siantar make up the population of this research. Students from classes XI PMIA 7 (experimental class) and XI PIS 2 (control class), who were chosen using purposive sampling technique and make up the sample for this research. There are 25 multiple choice questions on the research instrument, including pre-test and post-test that the researcher uses to assess the data. Researcher uses the t-test formula to analyze the data. The result of this data shows that the mean score of pre-test in experimental class score is 72.3 and mean score of post-test is 87.6. While in control class, mean score of pre-test is 70.97 and mean score of post-test is 78.28. After calculating the mean score for both groups and using the t-test formula, the results show that the t-test has the highest significance level in the t-table with 5% level significance (5.643 > 1.668). So, it is clear that Directed Reading Thinking Activity (DRTA) strategy has a significant effect on students' reading comprehension ability of recount text.